Ziwuliuzhu Acupuncture Modulates Clock mRNA, Bmal1 mRNA and Melatonin in Insomnia Rats - Ao Huang; Gefang Xiao; Yiliu Chen; Zuying Hu; Pin-Hsuan Lee; Yusen Huang; Zifeng Zhuang; Yuling Zhang; Peng Qing; Canghuan Zhao (Medical Association of Pharmacopuncture Institute, 2023)
Background : In clinics, Ziwuliuzhu acupuncture is widely considered an effective method of treating insomnia; however, there is currently limited information available regarding its possible mechanisms. Although the method of Ziwuliuzhu acupuncture possesses a unique rhythmic pattern. Objectives: In this study, we have creatively combined the traditional Chinese medicine of Ziwuliuzhu with a modern biological rhythm to investigate the internal mechanism of insomnia. Methods : Pathological tissue from the hypothalamus was analyzed using hematoxylin-eosin staining. The level of TNF (tumor necrosis factor)-α in the SCN (suprachiasmatic nucleus) area of the hypothalamus was detected in situ using the TUNEL fluorescence staining assay. The concentration of hypothalamic melatonin was detected using the enzyme-linked immunosorbent assay (ELISA). The mRNA expression of Clock and Bmal1 was measured using RT-qPCR. Results : In the Ziwuliuzhu acupuncture groups, the structural damage in the hypothalamic neurons was alleviated compared to the model group and the expression of inflammatory factors was reduced. The mRNA expression levels of Clock and Bmal1 were significantly increased (p < 0.05). The concentration of melatonin was significantly increased (p < 0.001). Although there were no significant differences between the treatment groups (diazepam group, Nazi group, Najia group, and routine group) (p > 0.05). Conclusion : Ziwuliuzhu acupuncture alleviated neuronal damage and modulated the inflammatory reaction in the hypothalamus of rats with insomnia. Moreover, Ziwuliuzhu acupuncture increased the expression levels of Clock and Bmal1 mRNA, and MT content. This study has potentially highlighted one of the mechanisms through which Ziwuliuzhu acupuncture can be used to treat insomnia.